1994
DOI: 10.1159/000246845
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis and Eczema Are Not Mutually Exclusive Diseases

Abstract: Background: Some reports have suggested that psoriasis and eczema are seldom found together. Knowledge of disease co-occurrence could lead to improved understanding of shared or opposing pathological mechanisms. Objective: We sought to determine whether psoriasis and eczema could exist simultaneously and consecutively in the same individuals. Methods: Skin examination data relating to 9,263 British children born during March 3rd to 9th, 1958 (the National Child Development Survey), were analysed for the co-occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 5 publications
2
19
0
Order By: Relevance
“…The mean age at onset is 28 years and only 35% of patients with psoriasis are diagnosed before 20 years of age 31 . A prevalence of 0·5% in 18‐year‐old Swedish men is similar to the 0·8% reported at the age of 16 in the U.K 32 …”
Section: Discussionsupporting
confidence: 74%
“…The mean age at onset is 28 years and only 35% of patients with psoriasis are diagnosed before 20 years of age 31 . A prevalence of 0·5% in 18‐year‐old Swedish men is similar to the 0·8% reported at the age of 16 in the U.K 32 …”
Section: Discussionsupporting
confidence: 74%
“…Among 1,701 patients with a firm diagnosis of atopic eczema, only five had concurrent psoriasis compared to an expected number of 125 patients. In contrast, a British study reporting from The National Child Development Survey of 1958 found an association between current atopic eczema and psoriasis at age 11 and 16 years [40]. These latter findings are consistent with the recent Scottish register-based study, which observed a strong association between current psoriasis and atopic eczema (the prevalence ratio of psoriasis in eczema patients was 2.88; 95 % CI 2.38 -3.45) [33].…”
Section: Atopic Eczema and Psoriasissupporting
confidence: 83%
“…The studies mentioned have several different limitations, including selection bias, which could be a serious and plausible limitation of the first study [15]; misclassification of diseases would be a plausible limitation of the two other studies [33,40].…”
Section: Atopic Eczema and Psoriasismentioning
confidence: 99%
“…Eczema refers to a group of acute and chronic, superficial, pruritic, inflammatory skin disorders characterized histologically by inflammation, intercellular edema (spongiosis), vesiculation, and parakeratosis. Although some reports suggest the two conditions are mutually exclusive, 9,10 larger studies show that they can occur concomitantly 11–14 …”
Section: Discussionmentioning
confidence: 99%